An intervention to improve sibling relationship quality among youth in foster care: Results of a randomized clinical trial. (January 2017) - Kothari, Brianne H.; McBeath, Bowen; Sorenson, Paul; Bank, Lew; Waid, Jeff; Webb, Sara Jade; Steele, Joel
Abstract: Sibling programming is an important part of a prevention framework, particularly for youth in foster care. After children are removed from their families and placed into foster care in the aftermath of maltreatment, the sibling relationship is often the most viable ongoing relationship available to the child, and may be critical to a youth's sense of connection, emotional support, and continuity. The promise of dyadic sibling programming in particular rests on the ability of interventions to enhance the quality of sibling relationships; yet little research exists that suggests that sibling interventions can improve relationship quality among foster youth. The primary aim of the current study was to examine the effects of a specific dyadic sibling-focused intervention for older and younger siblings on sibling relationship quality. One hundred sixty four dyads (328 youth) participated in the study, with each dyad consisting of an older sibling between 11 and 15 years of age at baseline and a younger sibling separated in age by less than 4 years. Hierarchical linear models were applied to self-reported, observer-reported and observational data over the 18-month study period. Findings suggest that the sibling intervention holds promise for improving sibling relationship quality among youth in foster care. Implications and future directions for research are discussed.